Evidentiranje delovnega časa po novem - Mašera, Damjan (Delavci in delodajalci, 2023)
The paper addresses amendments and additions to the Work and Social Security Records Act, and discusses shortcomings and problems that have been detected in the implementation of the law in practice and follow the initiative for amendments by the Inspectorate of the Republic of Slovenia for Work with a view to a more effective control over the implementation of legislation governing working hours, breaks and rest periods. Amendments to the law have been agreed upon by the social partners within the framework of the Economic and Social Council's negotiating working groups established for this purpose.
Keywords: control; credibility of records; delovna razmerja; Delovni čas; employment relationships; kadrovska evidenca; nadzor; records; social security; socialna varnost; working hours